Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis